2007
DOI: 10.1037/1064-1297.15.2.195
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of risk: A quantitative investigation into injection drug users' taxonomy of risk attitudes and perceptions.

Abstract: The authors report on the first study to use the systematic quantitative methods of the psychometric paradigm of risk analysis to examine risk perceptions among substance abusers. Fifty opioid-dependent injection drug users (IDUs) and 50 matched, control individuals completed a series of measures to provide quantitative representations of risk perceptions about 53 risk-laden items (including activities, substances, technologies, and diseases). Results indicated that risk perceptions of IDUs and controls were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…We expected more self-mastery and optimistic bias in this group because we hypothesized these factors would help explain continued cannabis use despite the likelihood of negative consequences. However, a study of optimistic bias in injection drug users showed no difference from controls for most imagined outcomes and that bias is actually less pronounced for potentially negative effects related to drug use (i.e., people using drugs agree that they are more vulnerable to negative outcomes from activities like unprotected sex compared to others (Marsch et al, 2007)). This study and our own results indicate that increased optimistic bias is not necessary for continued drug use and that bias among those with drug dependence may not differ from healthy controls in most instances.…”
Section: Discussionmentioning
confidence: 99%
“…We expected more self-mastery and optimistic bias in this group because we hypothesized these factors would help explain continued cannabis use despite the likelihood of negative consequences. However, a study of optimistic bias in injection drug users showed no difference from controls for most imagined outcomes and that bias is actually less pronounced for potentially negative effects related to drug use (i.e., people using drugs agree that they are more vulnerable to negative outcomes from activities like unprotected sex compared to others (Marsch et al, 2007)). This study and our own results indicate that increased optimistic bias is not necessary for continued drug use and that bias among those with drug dependence may not differ from healthy controls in most instances.…”
Section: Discussionmentioning
confidence: 99%
“…As LLAD lie at the intersection of stress and aging, agents that affect aging pathways (e.g. caloric restriction mimetics [Westphal et al ., 2007], superoxide dismutase mimetics [Quick et al ., 2008], CRF1 antagonists [Ising and Holsboer, 2007]) may pre-empt the adverse consequences of LLAD.…”
Section: Prospectusmentioning
confidence: 99%
“…This alternative aspect of impulsivity or the readiness to ''take risk''-is a complex psychological process that contributes to the make up of human personality (Evenden 1999). Individuals show great variation in their propensity to take risk Galvan et al 2007;Marsch et al 2007). Although impulsive behaviors are mostly known to be associated with negative consequences, ''risk taking'' may have conferred distinct advantage in reproductive success in nonhuman primates (Berard et al 1993;Mehlman et al 1995).…”
Section: Introductionmentioning
confidence: 99%